Progress towards a dengue vaccine. - Webster, D; Farrar, J; Rowland-Jones, S (2009)
The spread of dengue virus throughout the tropics represents a major, rapidly growing public health problem with an estimated 2.5 billion people at risk of dengue fever and the life-threatening disease, severe dengue. A safe and effective vaccine for dengue is urgently needed. The pathogenesis of severe dengue results from a complex interaction between the virus, the host, and, at least in part, immune-mediated mechanisms. Vaccine development has been slowed by fears that immunisation might predispose individuals to the severe form of dengue infection. A pipeline of candidate vaccines now exists, including live attenuated, inactivated, chimeric, DNA, and viral-vector vaccines, some of which are at the stage of clinical testing. In this Review, we present what is understood about dengue pathogenesis and its implications for vaccine design, the progress that is being made in the development of a vaccine, and the future challenges.